Pengaruh Viral Marketing, Harga Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Online Melalui Media Sosial Instagram - Duwi Mihartinah; Sularsih Anggarawati; Nasution Nasution (Universitas Bengkulu, 2023)
This study aims to examine the effect of viral marketing, price, and consumer belief on the online purchasing decisions through social media instagram in student of Bengkulu University. This research was conducted with a quantitative approach. The population in this study were student of Bengkulu University. Sampling using the sampling technique used in this study with proportiounate stratified random sampling. The number of samples of 265 respondents who were taken through a google form questionnaire using multiple regression analysis method. Based on statistical tests it was found that 1)viral marketing had a significant positive effect on the online purchasing decisions through social media instagram. This result means that if the maximize the use of viral marketing then the higher the effect on the online purchasing decisions through social media instagram. 2) price had a significant positive effect on the online purchasing decisions through social media instagram. This result means that if the higher the price match so that the online purchase decision will be higher. 3) consumer belief had a significant positive effect on the online purchasing decisions through social media instagram. This result means that the higher the consumer's trust, the higher the purchase decision. 4) Viral marketing, price, consumer trust have a significant simultaneous effect on online purchasing decisions through Instagram social media.